2011
DOI: 10.1161/circulationaha.110.947531
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 in Bone Marrow–Derived Cells Mediates Cardiac Repair After Myocardial Infarction

Abstract: Background The signaling mechanisms that regulate the recruitment of bone marrow (BM)-derived cells to the injured heart are not well known. Notch receptors mediate binary cell fate determination and may regulate the function of BM-derived cells. However, it is not known whether Notch1 signaling in BM-derived cells mediates cardiac repair following myocardial injury. Methods and Results Mice with postnatal cardiac-specific deletion of Notch1 exhibit similar infarct size and heart function following ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 52 publications
3
79
1
Order By: Relevance
“…In this respect, it should be considered that AAV vectors are outstanding tools for gene transfer into postmitotic cells and that their efficiency, in the heart, increases with terminal cardiomyocyte differentiation. 26 Thus, although our experiments rule out a direct effect of Notch pathway reactivation in driving adult cardiomyocyte proliferation in vitro and in vivo, they still remain compatible with the possibility that Notch signaling in adults hearts might exert beneficial effects in other cell types, such as in epicardial cells, 18 mesenchymal stromal cells, 16 bonemarrow-derived cells, 60 or cardiomyocyte precursors derived from cardiac stem cells. 9,17 Reactivation of Notch1 expression after MI in α-myosin heavy chain-mER-CremER transgenic mice showed a positive effect, which was mainly attributed to the preservation of cardiomyocyte viability and the stimulation of angiogenesis, with no evidence of a major regenerative effect.…”
supporting
confidence: 61%
“…In this respect, it should be considered that AAV vectors are outstanding tools for gene transfer into postmitotic cells and that their efficiency, in the heart, increases with terminal cardiomyocyte differentiation. 26 Thus, although our experiments rule out a direct effect of Notch pathway reactivation in driving adult cardiomyocyte proliferation in vitro and in vivo, they still remain compatible with the possibility that Notch signaling in adults hearts might exert beneficial effects in other cell types, such as in epicardial cells, 18 mesenchymal stromal cells, 16 bonemarrow-derived cells, 60 or cardiomyocyte precursors derived from cardiac stem cells. 9,17 Reactivation of Notch1 expression after MI in α-myosin heavy chain-mER-CremER transgenic mice showed a positive effect, which was mainly attributed to the preservation of cardiomyocyte viability and the stimulation of angiogenesis, with no evidence of a major regenerative effect.…”
supporting
confidence: 61%
“…[25][26][27][28] Previous studies showed crosstalks between Notch and other vascular signaling pathways in regulating arteriogenesis. 11 In tumor angiogenesis, inactivation of DLL4/Notch1 signaling inhibits tumor growth by promoting nonproductive angiogenesis. 7,29,30 Notch1 activation can induce neovascularization in the infarcted hearts and inactivation of Notch signaling leads to the inhibition of postnatal vasculogenesis in hindlimb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Notch1 receptor has been speculated to exert cardioprotection in injured myocardium, by controlling the cardiac adaptation to stress, enhancing myocyte survival, promoting precursor proliferation, and reducing fibrosis. 6,[9][10][11] DLL4/Notch1 activation is a requisite for the survival of hypertrophic myocardium and for the regeneration of damaged tissue. 6,9,12 On the contrary, inhibition of Notch1 signaling exacerbates cardiac hypertrophy, fibrosis, apoptosis, and dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that bone marrow mesenchymal stem cells (BMSCs) therapy has been widely applied in ischemic diseases such as myocardial and hepatic ischemia, through promotion of angiogenesis and suppression of apoptosis [1,2]. Meanwhile, BMSCs transplantation has been demonstrated to be an effective therapy for cerebrovascular diseases, which could promote endogenous neurogenesis and behavioral recovery [3].…”
mentioning
confidence: 99%
“…Once validated, TRPC6 may serve as a novel target in prevention and cure of MI. Keywords: Coronary Correlation Epicardial Myocardial blush TIMI frame count Videodensitometry TIMI frame count (TFC), was introduced in the early 1990s, as a method to assess the efficacy of thrombolysis and risk stratification in acute myocardial infarction (AMI) [1]. TFC proved to be a simple, reproducible, quantitative and objective method to evaluate epicardial flow not only in acute coronary syndrome settings, but in stable conditions with microvascular dysfunction, as well [2].…”
mentioning
confidence: 99%